Key factors supporting implementation of a training program for neonatal family- centered care - a qualitative study - Toivonen M; Lehtonen L; Ahlqvist-Bjorkroth S; Axelin A (BMC, 2025)
Background
Traditionally, the care of infants in neonatal care units has been professionally centered, paying less attention to family support. In recent years, many interventions have been developed to improve family-centered care and thereby parent and infant outcomes. Understanding the key factors of implementation of these interventions would help improve clinical practice. The aim of this study was to describe the staff's perceptions of the implementation of the Close Collaboration with Parents Training Program and to identify the barriers and facilitators of the implementation.
Methods
A descriptive qualitative interview study was conducted in eight neonatal intensive care units in Finland. Nineteen unit managers and 32 nurses were interviewed after their unit had finished the 1.5-year training program. Data were analyzed using thematic content analysis.
Results
Key factors facilitating the implementation of the training program were multidisciplinary commitment and the staff's motivation to change their professional role to work as the parents' facilitator. Observable benefits promoted the implementation, as well as experiential learning as a facilitation method. The role of mentor was remarkable as a facilitator. In addition, contextual elements such as support from leadership and proper timing were important.
Conclusions
Implementation of family-centered care is facilitated by staff who is prepared to accept parents as partners and adopt a new professional role. Enough time for preparation, readiness for the change, solid support from the leadership, and a multidisciplinary approach are needed as well. Mentoring was found to be one of the key factors facilitating the change.